Aggregation-induced emission luminogen with excellent triplet–triplet upconversion efficiency for highly efficient non-doped blue organic light-emitting diodes. Issue 1 (21st September 2021) - Han, Pengbo; Lin, Chengwei; Wang, Kaojin; Qiu, Yanping; Wu, Haozhong; Qin, Anjun; Ma, Dongge; Tang, Ben Zhong
Abstract : Highly efficient non-doped blue TTU-OLEDs were realized based on the AIEgens with excellent emission and upconversion efficiency in the film states. Abstract : By combining aggregation-induced emission (AIE) effect and a triplet–triplet upconversion (TTU) process, a blue emitter with excellent photoluminescence quantum efficiency and high upconversion efficiency in the film state is developed, from which a highly efficient non-doped blue TTU organic light-emitting diode (TTU-OLED) was realized.